Estudo das subpopulações linfocitárias em sangue periférico de pacientes com hanseníase - Solon, Vitória Régia Magalhães (2012)
Leprosy is a chronic infectious disease caused by the Mycobacterium leprae, a resistant alcohol-acid bacillus. It has a high infectivity, although the pathogenicity is low. Clinical manifestations present a great diversity. Host immune response is an important determinant of this clinical diversity, whilst lymphocytes collaborate to it. Thus, the present study aimed to describe lymphocyte subpopulations: T lymphocytes (CD3+), T helper lymphocytes (CD4+), T cytotoxic (CD8+), T CD4+CD8+, B (CD19+), Natural killers-NK (CD3- CD16+ CD56+) and T Natural killers - NKT (CD3+CD16+ CD56+) in peripheral blood samples from patients with leprosy, before and after the treatment with multidrugtherapy. Patients were selected at the Dona Libania Dermatology Center, at Fortaleza-CE, Brazil. The determination in each subpopulation of lymphocytes was done by flow-cytometer and statistical analysis by GraphPad Prism 5.0 for Windows. Significance was established at p values of <0.05. A total of 133 samples were studied, while 79 (59,4%) were males and 54 (40,6%)females. Median age of patients was 43 years old for the group before treatment and 46 years old for the group after treatment. Nine patients presented with paucibacillary and 124 with multibacillary form. NK (CD3-CD16+ CD56+) lymphocytes medians cells/mm³) were 142.0 [15,0–463,0] and 189,5 [18,0 – 1037,0], respectively for the groups before and after treatment, with a p value of 0.0484. On the other hand, no differences were observed when pauci and multibacillary groups were compared. T lymphocytes (CD3+), T helper lymphocytes (CD4+), T cytotoxic lymphocytes (CD8+), T (CD4+CD8+), B lymphocytes (CD19+) and NKT lymphocytes (CD3+CD16+CD56+)were similar at the groups before and after treatment and also at pauci and multibacillary. In conclusion, data from this study shows a reduction at NK lymphocytes (CD3-CD16+CD56+) populations in leprosy before any therapeutical intervention. After leprosy treatment, a recovery of this cell population occurs.